Desempenho de fungicidas no controle da mancha-de-macrospora na cultura do milho - Bampi, Daiana [UNESP]; Casa, Ricardo Trezzi; Bogo, Amauri; Sangoi, Luis; Sachs, Cristiano; Bolzan, Jonatha Marcel; Piletti, Giovani (FapUNIFESP (SciELO), 2012)
Fungicide application is one of the control strategies of fungal diseases in corn leaves. In Brazil, there are no fungicides recorded for the control of corn macrospora leaf spot (MLS). The aim of this study was to assess the efficacy of 16 fungicides on MLS control in a protective, curative and eradicant form. Fungicides of the chemical groups of benzimidazoles, strobilurins and triazoles were used alone or in mixture, in completely randomized block design, with six replicates of five plants, totaling 30 plants per treatment. The experiments were carried out in a greenhouse with the single-cross hybrid AS 1565 in phenological stage of two to six expanded leaves, using an isolate of S. macrospsora from the same hybrid. The inoculum was deposited into the cartridge of plants at 48 hours after, 48 hours before and 10 days before fungicide applications for preventive, curative and eradicant action, respectively. The experiment was repeated twice. The data underwent analysis of variance (p<0.05), and the means of treatments were compared by using the Scott-Knott test (p<0.05). Severity was estimated at 21 days after inoculations. All fungicides significantly differed from the control treatment in the preventive, curative and eradicant action. For the preventive action, mean disease control was 85%. The mixture of triazoles plus strobilurins controlled, on average, 75% of the disease severity, while the isolated products such as strobilurins reduced it by 62%, benzimidazoles by 55% and triazoles by 38% for the curative action. The lowest control was obtained for the eradicant action, with mean reduction of 40.1% in the disease severity and no significant difference among fungicides.
Fungicide performance on the control of macrospora leaf spot in corn
Keywords: Chemical control; Diplodia; Stenocarpella macrospora; Zea mays